The latest religious practices of da’i influencer and content creator in digital da’wah - Aida, Bakhita; Supena, Ilyas; Sulthon, Muhammad (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
Purpose - The aim of this research is to describe new religious practices in digital media. Method - Digital ethnography and literature review are the methods used in this research. Result - A new form of religious practice has emerged, conducted by influencers (A'yun, Ulfi, and Hijrapedia). This includes online muroja'ah, online Quran waqf, and online umrah substitutes. All three clearly indicate the existence of negotiations between offline and online spaces. Implication - This research definitively shows the shift from conventional preaching to digital methods without diminishing traditional religious authority. It is a definitive reference point for other new religious practices. Originality/Value - This research offers originality by revealing how digital media reshapes religious practices, introducing unique forms such as online muroja’ah, Quran waqf, and umrah substitutes led by influencers. It bridges the gap between traditional and digital spaces, challenging conventional sociological views and providing new insights into the evolution of religion in the digital age. *** Tujuan - Tujuan dari penelitian ini adalah untuk mendeskripsikan praktik-praktik keagamaan baru di media digital. Metode - Etnografi digital dan tinjauan literatur adalah metode yang digunakan dalam penelitian ini. Hasil - Bentuk praktik keagamaan baru telah muncul, yang dilakukan oleh para influencer (A'yun, Ulfi, dan Hijrapedia). Hal ini mencakup muroja'ah online, wakaf Alquran online, dan pengganti umrah online. Ketiganya dengan jelas menunjukkan adanya negosiasi antara ruang luring dan daring. Implikasi - Penelitian ini secara definitif menunjukkan pergeseran dari da’wah konvensional ke metode digital tanpa mengurangi otoritas keagamaan tradisional. Penelitian ini merupakan titik referensi yang pasti untuk praktik-praktik keagamaan baru lainnya. Orisinalitas/Nilai - Penelitian ini menawarkan orisinalitas dengan mengungkapkan bagaimana media digital membentuk kembali praktik keagamaan, memperkenalkan bentuk-bentuk unik seperti muroja'ah daring, wakaf Alquran, dan pengganti umrah yang dipimpin oleh influencer. Penelitian ini menjembatani kesenjangan antara ruang tradisional dan digital, menantang pandangan sosiologis konvensional dan memberikan wawasan baru tentang evolusi agama di era digital